2010
DOI: 10.4314/biokem.v21i2.56478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-trypanosomal Properties of Four Extracts of Leaves, Stem and Root Barks of <i>Prosopis africana</i> in Laboratory Animals

Abstract: Qualitative phytochemical and anti-trypanosomal properties of the petroleum ether, chloroform, methanol and aqueous extracts, obtained by cold extraction from the leaves, stem bark and roots of Prosopis africana were evaluated. The methanolic and aqueous extracts of the stem bark and leaves of the plant contained alkaloids, saponins, tannins and flavonoids. Anthraquinone was present in the stem bark methanolic extract and in the methanolic and aqueous extracts of the root as well as the aqueous extract of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…The significant suppression of T. congolense at 2000 mg/kg a day post therapy and at 1000 mg/kg on day 2, 3 and 4 is an indication that the ethanolic stem bark extract of C. swynnertonii possesses antitrypanosomal activity. Similar observations using extracts from different plants have been observed by other workers [29, 30]. Therefore, the current results confirm our earlier report which had similar results [21].…”
Section: Discussionsupporting
confidence: 94%
“…The significant suppression of T. congolense at 2000 mg/kg a day post therapy and at 1000 mg/kg on day 2, 3 and 4 is an indication that the ethanolic stem bark extract of C. swynnertonii possesses antitrypanosomal activity. Similar observations using extracts from different plants have been observed by other workers [29, 30]. Therefore, the current results confirm our earlier report which had similar results [21].…”
Section: Discussionsupporting
confidence: 94%
“…The observed activity of AA1 is supported by previous findings on the parasitocidal activities of A. leiocarpus and P. africana (1,22). The anti-malarial activity can be attributed to the presence of anti-infective phytochemical compounds such as alkaloids (prosopine and prosopinine), which have been found to be present in P. africana (1) and Castalagin isolated from Anogeissus leiocarpus (28). The injection of acetic acid into the peritoneum acts as a local irritant, triggering an inflammatory reaction that is characterized by the release of prostaglandins (PGE 2 , PGF 2α ), tumor necrosis factor (TNFα), and interleukins (IL-1β, IL-6), similar to endotoxin-induced inflammation in malaria.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is likely that AA1 and/or its active metabolites have a short biological half-life, which may have enabled the multiplication of recrudescent parasites after treatment; thus, changes in survival time of AA1-treated groups were insignificant compared with the untreated control (18). The observed activity of AA1 is supported by previous findings on the parasitocidal activities of A. leiocarpus and P. africana (1,22). The anti-malarial activity can be attributed to the presence of anti-infective phytochemical compounds such as alkaloids (prosopine and prosopinine), which have been found to be present in P. africana (1) and Castalagin isolated from Anogeissus leiocarpus (28).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, it has been reported that a complete elimination or reduction of motility of parasites when compared to the control could be taken as index of trypanocidal activity [21] . From the results in the present study, all crude extracts of P. bicalyculata: cold water, hot water, butanol and methanol extracts exhibited in vitro anti-trypanosomal activity against T. brucei brucei, however, the cold water extract was considered most active as it inhibited the 90% of the parasites after 60 min of incubation compared to other extracts.…”
Section: Discussionmentioning
confidence: 96%
“…The procedure was carried out separately for all extracts. A cessation or drop in motility of the parasites in treated blood compared to that of parasite-loaded control blood without extract was taken as a measure of anti-trypanosomal activity, since motility constitutes a relatively reliable indicator of the viability of most zooflagellate parasites [21] . The shorter the time of cessation of motility of the parasite, the more active the extract was considered to be [22] .…”
Section: In Vitro Anti-trypanosomal Screening Of Extracts and Fractiomentioning
confidence: 99%